Advantageous Selection in Insurance Markets with Compound Risk. Issue 2 (September 2017) - Huang, Rachel; Snow, Arthur; Tzeng, Larry
Abstract Building on the model of insurance contracting with hidden knowledge of risk class introduced by Rothschild and Stiglitz (1976), we assume that insurance applicants fail to reduce compound lotteries. In contrast with the adverse selection equilibrium identified by Rothschild and Stiglitz, in which coverage and expected claims frequency are positively correlated, we show that an advantageous selection equilibrium is possible, with coverage and expected claims frequency being negatively correlated. Whereas previous theories explain advantageous selection by adding a hidden action or a second dimension of hidden knowledge, our analysis shows that advantageous selection can arise solely as a consequence of insurance applicants' attitude toward bearing compound risks.